Fear of God: practicing emotion in late antique monasticism - An, Daniel E. (Christianity in late antiquity, 2025)
"In the writings of ancient Christians, the near-ubiquitous references to the 'fear of God' have traditionally been seen as a generic placeholder for piety. Focusing on monastic communities in late antiquity across the eastern Mediterranean, this book explores why the language of fear was so prevalent in their writings and how they sought to put it into practice in their daily lives. Drawing on a range of evidence, including sermons, liturgical prayers, and archaeological evidence, Daniel An explores how the languages monastics spoke, the socioeconomic settings they inhabited, and the visual spaces in which they prayed came together to shape their emotional horizons. By investigating emotions as practices embedded in the languages, cultures, and sensorial environments of late antiquity, this book offers new insights into the spiritual world of Christian monasteries"-- Provided by publisher